ANALISIS PERBANDINGAN EFISIENSI BANK UMUM SYARIAH (BUS) DAN UNIT USAHA SYARIAH (UUS) DENGAN METODE STOCHASTIC FRONTIER ANALYSIS (SFA) (Periode 2010-2013) - Haqiqi, Teuku Muhammad; Muharam, Harjum (Diponegoro Journal of Management, 2015)
Efficiency is one of parameter used for measuring banking performance. The purpose of this research is to analyze the efficiency of Islamic banking in Indonesia, particularly the Sharia Commercial Banks (BUS) and the Sharia Business Unit (UUS). There are 11 Islamic banks used as the sample of this research and divided into two groups of banks respectively 6 BUS and 5 UUS.This research uses Stochastic Frontier Analysis (SFA) methods with production function item as the measurement tools for Islamic banking efficiency level on BUS and UUS in Indonesian. Results of this SFA method appears in numeric score 0-1 form, the closer the result with score 1 the more Islamic banking approaches the perfect efficiency level. Input variables in this research are total deposits of third parties, total other operating expenses, and employee or labor cost. The output variable is total financing as the main product of Islamic banking. Variables were chosen based on intermediation approach. The independent sample t-test is used to find out the difference of efficiency level between each group of bank (BUS and UUS).The results of this research using SFA method shows that Islamic banking’s efficiency is increasing in every period between 2010-2013. The average efficiency on BUS and UUS respectively are 0,90098 and 0,901823. This suggests that UUS in Indonesian better than BUS during 2010-2013. Regarding the result of hypothesis testing panel about the influence of input variables toward BUS and UUS output variable, total deposits of third parties has positive and significant influence to the total financing, total other operating expenses has positive and insignificant influence to the total financing, and the employee or labor cost has negative and insignificant influence toward total financing. Independent sample t-test is used to gain the results of this different test hypothesis testing and it shows no difference in efficiency level between BUS and UUS.